Correspondance 1915-1963 - Poulenc, Francis 1899-1963; Milhaud, Darius 1892-1974; Wendel, Hélène de (Paris Seuil, 1967)
The correspondence between the famous French musician and a host of people, including other musicians (e.g. Milhaud, Stravinsky, Satie), poets (e.g. Cocteau, Max Jacob, Eluard), family members etc. The letters are to and from Poulenc.
Keywords: Satie, Erik -- 1866-1925; Stravinsky, Igor -- 1882-1971; Cocteau, Jean -- 1889-1963; 20th Century (1901-2000); Composer; Correspondence; France